Cisplatin-Induced Nephrotoxicity and HIV Associated Nephropathy: Mimickers of Myeloma-Like Cast Nephropathy - Muhammad Siddique Khurram; Ahmed Alrajjal; Warda Ibrar; Jacob Edens; Umer Sheikh; Ameer Hamza; Hong Qu (Case Reports in Nephrology)
Myeloma cast nephropathy is an obstructing disorder of renal tubules, caused by precipitation of Bence Jones proteins. Myeloma-like cast nephropathy (MLCN) has been reported in the literature to occur in various primary renal and nonrenal diseases. We present a series of three rare cases of cast nephropathy, two of which are HIV patients, and the third patient is receiving cisplatin-based chemotherapy. However, in all three patients plasma cell dyscrasia has been ruled out. A 30-year-old male was admitted to the hospital with facial cellulitis. The second patient is a 31-year-old male who presented with Pneumocystis jiroveci pneumonia. The third patient was treated with cisplatin-based chemotherapy for carcinoma. First two cases revealed foci of diffuse tubular dilatation containing hyaline casts and interstitial inflammatory infiltrate, in addition to globally sclerotic glomeruli with ultrastructural foot process fusion and mesangium expansion. The third case showed acute tubular injury and cast formation of irregular casts composed of amorphous or granular material of low density admixed with scattered high electron-dense globules. Myeloma-like cast nephropathy and true myeloma cast nephropathy pose similar destructive effects on renal parenchyma. This new pattern of HIV-related nephropathy should be considered in HIV patients with MLCN, once monoclonal gammopathy is ruled out.